Formation of the tooth-bone interface - Fleischmannova, J; Matalova, E; Sharpe, P T; Misek, I; Radlanski, R J (Journal of dental research, 2010)
Not only are teeth essential for mastication, but also missing teeth are considered a social handicap due to speech and aesthetic problems, with a resulting high impact on emotional well-being. Several treatment procedures are currently available for tooth replacement with mostly inert prosthetic materials and implants. Natural tooth substitution based on copying the developmental process of tooth formation is particularly challenging and creates a rapidly developing area of molecular dentistry. In any approach, functional interactions among the tooth, the surrounding bone, and the periodontium must be established. Therefore, recent research in craniofacial genetics searches for mechanisms responsible for correct cell and tissue interactions, not only within a specific structure, but also in the context of supporting structures. A tooth crown that is not functionally anchored to roots and bone is useless. This review aims to summarize the developmental and tissue homeostatic aspects of the tooth-bone interface, from the initial patterning toward tooth eruption and lifelong interactions between the tooth and its surrounding alveolar bone.
Keywords: signální transdukce; Periodontal Ligament; zubní zárodek; Tooth Germ; Osteoblasts; prořezávání zubů; Signal Transduction; odontogeneze; Osteogenesis; Tooth Root; periodontální vaz; Tooth Eruption; processus alveolaris; zubní korunka (anatomie); Animals; osteoblasty; osteogeneze; zvířata; Humans; Dental Cementum; Alveolar Process; Tooth Crown; zubní kořen; Odontogenesis; zubní cement (tkáň); lidé; homeoboxové geny; Genes, Homeobox